(untitled) (RIAF. International Journal of Physical Activity, 2023)
The process of training teachers in the university setting is one of the highest priorities of the Higher Education Institutions in the country, in correspondence with the socio-cultural, economic and technological changes, and their growing demands, from the point of view of from the point of view of how to achieve a higher quality of the training process of the university teacher. The objective of this study is to identify the epistemological dimensions applied by the university teacher. This study used a descriptive qualitative approach. It is concluded that initial training should provide foundations and reflective and critical attitudes that allow the professional to understand and interpret the educational reality and intervene in it. The findings highlight the need to open a debate on the possible improvements in the training process of the Physical Education teacher, which allows improving their personal competence to promote their enthusiasm for teaching this discipline, which allows the understanding of the epistemological dimensions that emphasizes the pedagogical performance of the teacher as a mediator of the autonomy of their students.